Hypopituitarism Induced by Continuous Infusion of PGI2 Analogues: A Case Series and the Role of ACTH Screening and Hydrocortisone Treatment - Taijyu Satoh; Yuichi Tamura; Noriaki Takama; Hiromi Matsubara; Nobuhiro Tanabe; Takumi Inami; Takahiro Hiraide; Kohtaro Abe; Yoshihiro Dohi; Yoshito Ogihara; Takeshi Ogo; Shiro Adachi; et al. (Pulmonary Circulation)
ABSTRACT Hypopituitarism has been reported in patients receiving continuous infusions of prostaglandin I2 (PGI2) analogues for pulmonary hypertension (PH). However, these patients' clinical characteristics, treatment, and prognoses remain unclear. This retrospective multicentre study included 22 patients who developed hypopituitarism while on continuous PGI2 analogue infusion between 1999 and 2021. All patients were female, and idiopathic pulmonary arterial hypertension was the most common underlying condition (63.6%). Their mean age was 38.8 ± 7.9 years. Epoprostenol was the predominant PGI2 analogue used (90.9%). At the time of hypopituitarism onset, the median PGI2 dose was 67.2 ng/kg/min (31.8–88.7 ng/kg/min), and the median treatment duration was 889.0 days (450.5–1941.5 days), suggesting that hypopituitarism occurred independent of its dose or treatment duration. Diagnoses were based on decreased adrenocorticotropic hormone levels. The hypopituitarism classification revealed isolated pituitary dysfunction in 54.5% of the cases, partial dysfunction in 18.1%, and complete dysfunction in 27.2%. Most cases could be managed without requiring specific therapies. After hypopituitarism onset, 63.6% of the patients continued to receive the same PGI2 analogue. Hydrocortisone therapy was administered to 81.8% of the patients, leading to clinical stabilisation. No deaths were reported. In conclusions, hypopituitarism may occur during continuous PGI2 analogue infusion for PH, irrespective of its dose or treatment duration. Initiating hydrocortisone therapy may be important for stabilising the clinical course.